Mean Urea Reduction Ratio among Patients Undergoing Hemodialysis at a Tertiary Care Centre: A Descriptive Cross-sectional Study - Krishna Kumar Agrawaal; Sanjog Kandel; Sudhan Devkota (Journal of Nepal Medical Association, 2023)
Introduction: Chronic kidney disease is a major cause of mortality with a prevalence of 6%. Over the past half-century, hemodialysis has been the most preferred modality of treatment for sustaining the life of patients with end-stage kidney disease. Despite hemodialysis being freely available, achieving adequacy in hemodialysis is a challenging task. Inadequate dialysis is responsible for the high mortality. This study aimed to find out the mean value of the urea reduction ratio among patients undergoing hemodialysis at a tertiary care centre.